Malignant Hypertensive Retinopathy in an Infant with Mid-Aortic Occlusion - Lawrence J. Oh; Gaurav Bhardwaj; David S. Winlaw; Craig E. Donaldson (Case Reports in Ophthalmological Medicine)
Purpose. Case report describing an eight-month-old infant presenting with intermittent esotropia and irritability who was found to have malignant (grade 4) hypertensive retinopathy and mid-aortic syndrome. Methods. Visual acuity was 6/140 in the right eye and not recordable in the left eye. Blood pressure was as high as 230/120 mmHg. Fundoscopy revealed bilateral optic disc swelling, macular stars, and serous retinal detachment in the left eye, findings that are consistent with malignant (grade 4) hypertensive retinopathy. CT abdominal angiogram revealed a severe mid-aortic syndrome with occlusion of the abdominal aorta at T12. Results. The patient was treated with medical management of his hypertension, improving the subretinal exudate. Binocular visual acuity improved to 6/9.5 over 9 months. There was a persistent left relative afferent pupillary defect and moderate left esotropia. Conclusion. This is the first reported case of malignant hypertensive retinopathy in an infant with concomitant mid-aortic occlusion. The authors emphasize the need for an ophthalmological and pediatric examination in a child presenting with intermittent squint and irritability. The esotropia was found to be a false localizing sign of raised intracranial pressure secondary to the severe mid-aortic syndrome.